Exploring the Role of Digital Forensics in Identifying Cyber Crime in Indonesia's Criminal Procedure Law - Monique, Cindy; Yuliati, Yuliati; Sulistio, Faizin (Faculty of Law, Universitas Pekalongan, 2024)
Digital forensics is an indispensable component in the process of detecting and examining cybercrimes in accordance with the Criminal Procedure Law of Indonesia.This study investigates where digital forensics fits into Indonesia's Criminal Procedure Law for cybercrime detection. As cybercrime rises, it's important to understand how digital forensics can investigate and prosecute cybercrimes. This study examines Indonesian digital forensics law and practice using normative legal research. The author employs normative legal research procedures in this specific legal study. This study found that due to laws, Indonesia needs digital forensics to protect electronic evidence. Treat electronic evidence differently than physical. Indonesian courts' use of digital forensics is valued since cybercriminals can tamper with electronic evidence. The processes manage cybercrime electronic evidence legally. Validation of criminal procedure. Criminal procedural laws must be enforced by police, prosecutors, legal experts, and judges. Police should standardize electronic evidence management with digital forensics. In wealthier nations like the US, digital forensics protects electronic evidence